1973
DOI: 10.1080/03036758.1973.10430596
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic study by computer analysis of marine bacteria from New Zealand waters

Abstract: One hundred and fifty-five strains of marine bacteria have been isolated from oceanic waters in the New Zealand region, at depths from 50 to 2000 m. A further 36 luminous strains were isolated from light organs and intestines of fish. All isolates were characterised using a series of morphological, physiological, and biochemical tests, and the results of these tests were subjected to numerical analysis using a digital computer to group the strains according to the similarity of their features. This sorting pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…P.p/zosplzorezm has already been isolated from water and light organs of fish at depths from 50 to 2000 m in Newzealand waters (SINGLETON and SKERMAN 1973). OHWADA et af.…”
Section: Vertical Distrihutiorimentioning
confidence: 99%
“…P.p/zosplzorezm has already been isolated from water and light organs of fish at depths from 50 to 2000 m in Newzealand waters (SINGLETON and SKERMAN 1973). OHWADA et af.…”
Section: Vertical Distrihutiorimentioning
confidence: 99%
“…Overview of Photobacterium and the bacterial luminescence (lux) genes symbiosis with certain shallow-dwelling fish and squid, whereas Photobacterium phosphoreum typically occurs in mesopelagic, colder marine waters and has not been identified from bioluminescent symbiosis (e.g. Reichelt & Baumann, 1973;Singleton & Skerman, 1973;Ruby & Morin, 1978;Yetinson & Shilo, 1979;Ruby et al, 1980;Yang et al, 1983;Dunlap et al, 2007). Many members of this clade associate with marine animals, as commensals, saprophytes, bioluminescent symbionts, or pathogens; like other members of Vibrionaceae, they presumably transit between seawater, possibly a starvation-survival habitat (Morita, 1997), and host animals, a nutrient-rich habitat that supports reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Equally important will be analysis of multiple genetic loci, to assess the robustness of phylogenetic inference based on individual loci, and examination of rapidly diverging loci, to trace the evolutionary history of a clade and its close relatives. Previous studies have noted differences between the P. phosphoreum type strain, ATCC 11040 T , and other strains identified phenotypically as members of this species (6,22,41,45), possibly presaging the genotypic results presented here. More recently, a study of strains of luminous bacteria from the skin of migrating salmon revealed a possible parallel to results presented here; analysis of the luxA gene sequence showed an apparent phylogenetic distinction between NCIMB 844 and the strains from salmon skin, which were identified phenotypically as P. phosphoreum, whereas analysis of the 16S rRNA gene did not distinguish those strains from ATCC 11040 T (5).…”
Section: Discussionmentioning
confidence: 75%
“…Members of six teleost families representing four orders, i.e., Opisthoproctidae (Osmeriformes), Chlorophthalmidae (Aulopiformes), Macrouridae, Steindachneriidae and Moridae (Gadiformes), and Trachichthyidae (Beryciformes), have been reported to harbor luminous bacteria identified as or thought to be P. phosphoreum (2, 14-16, 21-26, 28, 42, 44, 45, 48, 56, 61). As a psychrotrophic species, P. phosphoreum may be adapted thermally to symbiosis with these fishes, which occur in deep, cold marine waters (9,17,19).Detailed taxonomic study has been conducted on bacteria from certain of these fishes (22,44,45). In most cases, however, the identification of the bacteria as P. phosphoreum is based on limited or unreported taxonomic data and on the examination of few strains.…”
mentioning
confidence: 99%
See 1 more Smart Citation